A survey of knowledge about hepatitis B among new military recruits in China. Issue 1 (December 2017) - Li, Yuan-Yuan; Chen, Wei-Wei; Wei, Lei; Xie, Yang-Xin; Wang, Li-Feng; Fu, Jun-Liang; Wang, Fu-Sheng
Abstract Background Hepatitis B is a disease that affects the liver and is caused by the hepatitis B virus (HBV). Hepatitis B is a serious public health problem in China. The objective of this study was to assess knowledge of and behaviours towards the transmission and prevention of hepatitis B of new military recruits in China. Methods A cross-sectional study was conducted among 800 new military recruits. A self-administered, structured questionnaire was used to collect information, and 727 questionnaires were returned completed. Analysis was performed using SPSS 18.0, andP  < 0.05 was considered statistically significant. Results Of the respondents, 665 (91.5%) were male and 62 (8.5%) were female. The mean age was 18.9 ± 1.7 years. A total of 608 respondents (83.6%) demonstrated poor knowledge and 119 (16.4%) adequate knowledge about HBV. Older age, female and higher education level were statistically associated with a higher mean knowledge score. Multivariate logistic regression showed that age (OR  = 3.040, 95%CI 1.724–5.359, P  < 0.001) and gender (OR  = 1.791, 95%CI 1.325–2.421, P  < 0.001) were significantly associated with appropriate behavioural practices towards prevention of HBV. Conclusion Against a backdrop of high HBV prevalence in China, new military recruits had poor knowledge of HBV. New recruits need better education about HBV to assist in reducing and preventing HBV infection.